The Impact of the Closure and Reopening of Golf Courses in the United Kingdom on Wellbeing During the COVID-19 Pandemic: A Multi-Study Approach - Sorbie, Graeme G.; Beaumont, Alexander J.; Williams, Ashley K.; Glen, Jonathan; Hardie, Scott M.; Lavallee, David (Frontiers in Sports and Active Living, 2021)
The purpose of this multi-study was to assess what impact the closure and reopening of golf courses had on: personal competence; sense of belonging; enjoyment; self-esteem; self-confidence; resilience; social connections; wellbeing and life satisfaction (hereafter referred to collectively as ‘key variables of interest’) during the COVID-19 pandemic. Golfers (Study 1: n = 298, Study 2: n = 124) ≥ 16 years old residing in the UK participated in this study which collected data using online surveys. Study 1 was conducted during a period of quarantine restrictions (4 – 12th May 2020), whilst study 2 took place following the easing of the COVID-19 quarantine restrictions (6 – 14th July 2020). Within study 1 and study 2, key variables of interest levels were also collected to investigate the association with golf related activities. The findings of study 1 highlighted that negligible and non-significant correlations were observed between golf physical and sedentary activities and key variables of interest (r < 0.3, p > 0.05) except sense of belonging and sedentary golf activities (r = 0.178, p = 0.003). Study 2 highlighted that sense of belonging, enjoyment and wellbeing were significantly associated with outdoor golf course activity (r = 0.186 – 0.252, p ≤ 0.05). Furthermore, when comparing study 1 and study 2, sense of belonging and life satisfaction significantly improved (p ≤ 0.05, d = 0.2). Based on these findings, playing golf on outdoor golf courses appears to be positively related to sense of belonging, enjoyment and wellbeing. Also, with the reopening of golf courses life satisfaction improved which, together, highlight the beneficial impact that outdoor golf can impart.